Natural resources management in African agriculture: understanding and improving current practices - Barrett, C. B.; Aboud, A. A.; Aboud, A. A.; Barrett, C. B.; Place, F.; Place, F. (Wallingford :CABI Publishing, 2002)
This book synthesizes existing information on the adoption of natural resource management investments and strategies (such as soil fertility improvements or erosion control) for agriculture in sub-Saharan Africa. It also critically examines current analytical methods and generates research and policy recommendations. Topics covered include: farmers' objectives and learning processes; willingness and capacity to make long-term investments; economic incentives and the importance of the resource base; and the agroecological, institutional and policy contexts. The book has 22 chapters and a subject index.
Keywords: CC200 - Extension and Advisory Work; EE110 - Agricultural Economics; EE115 - Natural Resource Economics, (New March 2000); EE120 - Policy and Planning; JJ600 - Soil Fertility; JJ800 - Soil Water Management (Irrigation and Drainage), (Revised June 2002); JJ900 - Soil Management; KK600 - Agroforestry and Multipurpose Trees: Community, Farm and Social Forestry; PP400 - Erosion: Soil and Water Conservation; Africa South of Sahara